Extensive examination of sonication duration impact on stability of Al2O3-Polyol ester nanolubricant - A., Nugroho; Z., Bo; R., Rizalman; W. H., Azmi; G., Najafi; F., Khoirunnisa (Elsevier, 2021)
The sonication technique is one of the effective methods to stabilize nanolubricants. This paper aims to elaborate on the sonication duration’s impact on the stability of Al2O3-Polyol ester nanolubricants. A two-step method has been performed to prepare nanolubricants. Each sample consisted of a nanoparticle mixed with POE using a magnetic stirrer without surfactant for 30 min. All samples had the same volume concentration, namely 0.02 vol % but received different interlude sonication duration treatments for 0, 40, 60, 80, 100, and 120 min. FESEM with Energy Dispersive X-Ray was used to characterize the Al2O3 nanoparticle sample’s morphology and element analysis. UV Visible and absolute zeta potential were used to determine Al2O3-POE nanolubricants stability. The findings show that the most optimal sonication impact in this study is 80-min sonication. It proofed by the highest absorbance ratio among other samples, which is 0.411, the lowest drop absorbance value, which is 58.9%, and and with a zeta potential value of 45 mV. The rheological behavior analysis shows that Al2O3-POE nanolubricants show Newtonian behavior.